Dinasti Mughal Dan Kemunduran Islam Di India Tahun 1525-1857 M - Zalukhu, Derita Murni (Universitas Cokroaminoto Yogyakarta, 2024)
The History of Islam in India was characterized by changes in countries that entered India to spread various teachings and increase cultural differences. One of the spreads of religion that was very easy to understand in India at that time was the teachings of Islam and the development of various kingdoms, one of which was the Mughal dynasty. The founder of the Mughal dynasty who initially succeeded in establishing Islam in India was Kutbu'ddin Aibak. Of the several leaders of the Mughal Dynasty, there were only three leaders during which the Mughal Empire reached its heyday, namely Aurangzeb, Shah Jahan and Sultan Akbar. The method for writing this article is library research. This data is collected through several sources such as journals, articles and books according to what we use. The results of this research include 1) the founding of the Mughal dynasty, 2) the leaders of the Mughal dynasty from its inception until its decline, 3) the historical remains of the Mughal dynasty, 4) factors that caused the decline of the Mughal dynasty.